DINAMIKA MODAL SOSIAL NELAYAN DALAM ARENA EKONOMI: Studi Kasus Nelayan Rajungan Desa Betahwalang, Kecamatan Bonang, Kabupaten Demak - Joni Trio Wibowo; Rilus A Kinseng; Titik Sumarti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Relations in the fishermen community of Betahwalang village are shown in economic field and non economic field. The strong network and social norm within community enable fishermen community members to confineand to direct actions of actors within the group. Fishermen of Betahwalang are able to separate economic field and non economic field by logic of separation. This research aims to understand the dynamic of fishermen’s social capital in economic arena. Qualitatively, this study finds dynamic relationship in economic field in blue swimming crab fishermen community of Betahwalang village. Economic action is the actions of individual to maximize profits for themselves. Collaboration in economic field can occur in low level of trust, strong norms and network. In contrast, Sosial capital form different element of capital (i.e. trust, norms and networks) in different sosial situations (i.e. cooperation, competition or conflict).